Microbial Keratitis After Corneal Collagen Cross-Linking for Corneal Ectasia. Issue 4 (July 2021) - Khoo, Pauline; Cabrera-Aguas, Maria; Watson, Stephanie L.
Abstract : Purpose: The aim of this study was to report the clinical profile and microbiological of patients with microbial keratitis post accelerated corneal collagen cross-linking (CXL). Methods: A retrospective case series of all patients diagnosed with microbial keratitis post-CXL who attended the Sydney Eye Hospital, Australia from January 1, 2012 to December 31, 2019 were included. Patients were identified from hospital coding and pathology data. Data were extracted from patients' medical records. Results: Eleven eyes from 10 patients with a mean age of 29 ± 11 years (range 16–48) were included. The median time of infection after CXL surgery was 4 days [interquartile range (IQR) 3–83]. Median initial and final Visual acuity at presentation were 1.3 logMAR (IQR 1–2.0) and 0.8 logMAR (IQR 0.6–1.2), respectively. The culture positivity rate was 92%, identifying 13 isolates, predominately made up of coagulase-negative Staphylococcus (n = 6, 50%) and Staphylococcus aureus (n = 3, 25%). The median epithelial healing time was 30 days (IQR 15–53). Conclusions: Post-CXL microbial keratitis was predominately associated with gram-positive bacteria and in some cases delayed epithelialization. Microbial keratitis post-CXL may lead to moderate to poor patient outcomes.